Navigating Sustainability: A Comparative Analysis of SDG Performance in the GCC through the Lens of Social Capital Theory - Aldulaimi, Saeed Hameed; Abu-AlSondos, Ibrahim A.; Noun, Rola; Abdeldayem, Marwan M. (Journal of Management World, 2025)
This study aims to review and analyze the progress of Sustainable Development Goal (SDG) performance as per the UN dashboard. This approach seeks to bolster the necessary capabilities for the effective implementation of sustainable projects, enhance efficiency in resource management, and achieve environmental and social objectives. Employing a comparative study method, the research delves into various facets to scrutinize the challenges of implementing sustainability guidelines in the Gulf Cooperation Council (GCC). Drawing upon the dual perspectives of constraining and expanding egos rooted in social capital theory, the study aims to offer strategic assessments and policy implications regarding key sustainability issues. By aligning with the overarching objectives of National Vision 2030 and fostering long-term sustainable development in the region, this research scrutinizes pivotal indicators and correlates them with key strategies for national advancement, while analyzing significant events and shifts in strategy alongside associated challenges.